Influence of the physical and psychological variables on physical injuries in football - Fernández Garcia, R.; Zurita Ortega, F.; Cepero González, M.; Molina Garcia, V. A.; Vilches Aznar, J. M.; Ambris Sandoval, J. (Journal of Human Sport & Exercise, 2015)
Over the years, a great number of studies have examined the importance of preventing sports injuries and developing effective physical procedures and psychological techniques for the recuperation of the injured athlete. The present study evaluates the effect of age, category, equipment, and anxiety/feature in the occurrence of injuries in football (soccer). A total of 277 players from 26 different football teams of Ciudad del Carmen (Mexico) participated in the study. Data on the variables of interest were compiled by the self-recording of sports injuries together with the questionnaire STAI-RASGO. The results did not reflect statistically significant differences between the variable sports injury and age, category, and anxiety/feature, respectively (p=.542; p=.127; p=.598); significant differences were found only in the relation sport and team (p< .001). We conclude that the cause of sports injuries is multifactorial and therefore interdisciplinary work is fundamental, such as the development of programmes that approach the athlete from an integral standpoint.